2019
DOI: 10.1016/j.cell.2019.02.030
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Receptor Associates with Promoters Genome-wide and Regulates Gene Expression

Abstract: Highlights d Cell-surface IR translocates to the nucleus and associates with promoters genome-wide d IR interaction with DNA is mediated by coregulator HCF-1 and transcription factors d IR associates with Pol II and regulates gene expression d Target genes are characteristic of insulin functions in physiology and disease

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
117
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(126 citation statements)
references
References 68 publications
1
117
0
1
Order By: Relevance
“…Unexpectedly, treatment with PEG-insulin elicited a β-cellspecific stimulation of the insulin signalling cascade as well as stimulation of the recently characterised RNA polymerase II mediated pathway 41 (Fig. 6h).…”
Section: Ucn3mentioning
confidence: 88%
“…Unexpectedly, treatment with PEG-insulin elicited a β-cellspecific stimulation of the insulin signalling cascade as well as stimulation of the recently characterised RNA polymerase II mediated pathway 41 (Fig. 6h).…”
Section: Ucn3mentioning
confidence: 88%
“…In rat hepatocytes, INSR has been shown to translocate to the nucleus where it regulates calcium signals and proliferation (32). Hancock and colleagues have also investigated the role of INSR in the nucleus of mouse liver cells (33). In their studies, they found that INSR directly associated with genome-wide promoters and regulates gene expression through interactions with RNA polymerase II.…”
Section: Intracellular Igf-1r Insr and Hybrid-rmentioning
confidence: 99%
“…The most wellstudied example is the forkhead family box O (FOXO) transcription factors which, upon insulin stimulation, are phosphorylated by AKT, bind to 14-3-3 proteins and are thus excluded from the nucleus, limiting their ability to regulate gene expression. 3 Insulin also promotes phosphorylation of FOXK transcription factors 4 and phosphorylation and processing of SREBP-1c, 5 but in these cases, this promotes migration of the FOXKs and SREBP1c into the nucleus where they can regulate transcription.In a recent paper in Cell, Hancock et al 6 propose a new model of insulin regulation of transcription in which IR itself translocates to the nucleus, where it interacts with RNA polymerase II (Pol II) on gene promoters and induces transcription ( Fig. 1, right).…”
mentioning
confidence: 99%
“…These IRbound promoters were highly enriched for genes known to be involved in insulin functions in liver, including lipid metabolism, protein synthesis and transcription, as well as for disease pathways where IR signaling is typically dysfunctional such as diabetes and Alzheimer's disease. On the other hand, these sites did not include genes involved in pathways of glucose metabolism, such as gluconeogenesis and glycogen synthesis, which are major metabolic functions of insulin in liver.Through a combination of motif analysis and mass spectrometry, Hancock et al 6 found that the transcriptional coregulator host cell factor-1 (HCF-1) is required for the assembly of IR transcriptional complexes, on at least a subset of genes. Since HCF-1 lacks direct DNA-binding activity, an important step moving forward will be to determine the DNA-binding proteins and transcription factors that mediate IR-HCF-1-Pol II complex formation, how these are regulated and what genes they regulate.…”
mentioning
confidence: 99%
See 1 more Smart Citation